PENENTUAN BREAK EVEN POINT MELALUI REGRESI DAN NEWTON RAPHSON - Fitroh Resmi; Aris Alfan; Nihaya Alivia Coraima Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Determining Break Even Point (BEP) in a production is an important thing to do. BEP analysis is used as a basis for profit planning. By knowing the Break Even Point (BEP), management can determine the amount of production or sales that must be made according to the profit target to be achieved. The research method used is literature review (literature study). Data collection techniques using secondary data taken from the Kaggle site. Data analysis uses descriptive statistics with the help of the python program. In certain cases, the production costs or selling cost is not a linear function. So it is necessary to form a mathematical equation through regression. The model is evaluated using MAE, MSE and R2. Determination of BEP is done by forming the equation of production costs and selling costs which are then solved by the Newton Raphson method. The results of this study are the regression method and Newton raphson can be used as an alternative in determining the BEP for cases that are not linear.